THE CRYSTAL STRUCTURE OF PARANATROLITE - Seryotkin Y.V.; Belitsky I.A.; Bakakin V.V. (My University, 2004)
Paranatrolite from the Khibiny massif, Kola Peninsula, Russia, Na1.88K0.22Ca0.06[Al2.24Si2.76O10](.)3.1H(2)O, is monoclinic (space group Cc, Z = 4). For better comparison of this mineral with the related structure of natrolite, we have selected. a pseudoorthorhombic setting in F1d1 (a = 18.971(4), b = 19.204(3), c = 6.5952(12) Angstrom, beta = 91.601(18)degrees, Z = 8). The dominant Na+ cations are situated near the sodium positions in the natrolite structure. Additional positions occupied by K+ are located in the eight-membered rings. H2O molecules are located in four independent positions, two being occupied statistically. The Na-polyhedra correspond to distorted NaO3(H2O)(3) octahedra forming chains along the c axis by sharing common H2O-H2O edges and H2O vertices. The availability of potassium in the structure results in two configurations for the coordination environment of Na+.
Keywords: Paranatrolite